Chitin formation and diagenesis - Gupta, Neal S.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
There are several books on properties of chitin and associated biomolecules and their biochemical significance. However, the present volume deals with a wide variety of biogeochemical and organic geochemical aspects of this vital macromolecule written by leading authors and experts in the field. Each chapter is carefully peer reviewed and is an updated account of recent research in isotopic, nanostructural, biochemical, microstructural, geochemical, paleontological and experimental aspects of chitin formation, distribution and preservation in the environment and earth history.
1. Chitin nanostructures in living organisms.-2. Chitin in the exoskeletons of Arthropoda: From ancient design to novel materials science -- 3. Radiocarbon Dating of Chitin -- 4. Carbon, nitrogen and oxygen stable isotope ratios in chitin -- 5. Hydrogen Isotopes in Beetle Chitin -- 6. Identification and characterization of chitin in organisms -- 7. Fate of chitinous organisms in the geosphere -- 8. Transformation of chitinous tissues in elevated Presssure-Temperature conditions: additional insights from experiments on plant tissues.
Electronic reproduction.
Keywords: Chitin; Arthropoda -- Anatomy; Arthropoda -- Physiology; Organic geochemistry; Electronic books